Biodegradation of 2-chlorophenol using free and immobilized laccase from Trametes Versicolor / Swapna Sambrani - Swapna, Sambrani (2009)
Laccase from white rot fungus Trametes versicolor was immobilized in sodium alginate beads using entrapment method. Kinetic parameters (Vmax and Km) of both free and immobilized laccase were determined using syringaldazine as substrate. 2- chlorophenol was degraded using free and immobilized laccase. An indirect rapid assay method was developed for the assay of degraded products of 2-chlorophenol, wherein the anionic phenoxy radicals, possibly generated during 2-chlorophenol degradation, couples with a cationic dye, Methylene Blue and renders it colorless. The extent of decolorization indicated the extent of product formation and hence the extent of 2-chlorophenol degradation assuming a 1:1 stoichiometric reaction between degraded products of 2- chlorophenol and the dye. Factors like pH, temperature and enzyme concentration were optimized for the free enzyme reaction and reaction time, temperature and enzyme concentration were optimized for the immobilized enzyme reaction using a statistical tool viz. Box-Behnken method of Response Surface Methodology. The efficiency of immobilized laccase with respect to 2-chlorophenol degradation was found to be comparable to that of free laccase. External mass transfer was found to have negligible effect on the diffusion of substrate from bulk liquid to the surface of the bead while there was significant limitation posed by internal mass transfer from the surface of the bead to the center of the bead.